2013
DOI: 10.1590/s0370-44672013000400015
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic scavenging of ultrafine hematite from itabirites

Abstract: ResumoA separação magnética industrial tem ganhado força com o advento de equipamento contínuo com alto gradiente de campo. A recuperação magnética de hematita contida em lamas espessadas é aqui discutida, a partir de ensaios comparativos em escala-piloto com três separadores de alto gradiente, simulando a adoção de um circuito de esgotamento (seguido de limpeza do concentrado). Dois separadores magnéticos de rotor em anel horizontal (tipo carrossel) -rotulados como W1 e W2 -e um de rotor em anel vertical e pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Several authors have demonstrated a series of new technologies that could enhance magnetic separation processes through the development of new characterization techniques [27], equipment's [28][29][30][31][32][33][34] and the use of different matrices in high-intensity magnetic separation [35][36][37][38][39]. Such alternatives may result in significant gains in capacity, fines recovery, quality, and metallurgical recovery, as they make use of existing capacity and require low capital investment.…”
Section: Otimização Da Separação Magnética Da Hematita Contida No Pro...mentioning
confidence: 99%
“…Several authors have demonstrated a series of new technologies that could enhance magnetic separation processes through the development of new characterization techniques [27], equipment's [28][29][30][31][32][33][34] and the use of different matrices in high-intensity magnetic separation [35][36][37][38][39]. Such alternatives may result in significant gains in capacity, fines recovery, quality, and metallurgical recovery, as they make use of existing capacity and require low capital investment.…”
Section: Otimização Da Separação Magnética Da Hematita Contida No Pro...mentioning
confidence: 99%
“…The opposite is observed with quartz (25.5 wt%) and hematite (6.8 wt%) contents. Based on the mineralogical composition of the studied sample, the magnetic concentration of medium-to-high field is the most suitable concentration method for this type of ore [6][7][8][9]. As can be observed in the thermogram (Figure 4) is the first region of weight loss up 200 • C due to the loss of physically adsorbed water by the van der Walls bond (environment temperature), which is removed by air purging of the sample and hydrogen bonds on goethite [21][22][23][24][25][26][27].…”
Section: Physical Characterizationmentioning
confidence: 99%
“…The Fe grades of this material are between 30-53%. Silva and Luz [8] carried out the magnetic concentration of a slime thickener underflow sample (100% −150 µm, with grades of 32.9% Fe, 37.7% SiO 2 , 5.3% Al 2 O 3 and 5.7% loss on ignition-LOI)) from a mine located in Quadrilátero Ferrífero. The magnetic field intensities tested were of 0.6, 0.9 and 1.2 T. The best result after a cleaner step was obtained with a magnetic field of 1.2 T: 64.6% Fe, 5.5% SiO 2 and a mass recovery of 62.8%.…”
Section: Introductionmentioning
confidence: 99%